Animal Pesticide Poisoning in Tunisia - Lahmar, Rym; Berny, Philippe; Mahjoub, Tarek; Ben Youssef, Samir (Frontiers in Veterinary Science, 2019)
A retrospective study on pesticide poisonings in domestic animals and livestock from 2014 to 2017 submitted to the Pharmacy and Toxicology Laboratory of the School of Veterinary Medicine of Sidi Thabet in Tunisia, was compiled then analysed. During this period, a total of 71 pesticide analysis requests has been referred mainly by the Pathology Laboratory in the same School, by veterinary practitioners, regional and central governments and private owners. Among the total number of the suspected samples, 21 (29.6%) cases were found positive to contain various kinds of pesticides. Carbamate insecticides were The most frequently implicated pesticide, representing 52.4% of the total positive cases. This compound was followed by organophosphate insecticides (19%), then by rodenticides-anticoagulants and rodenticides non-anticoagulants with 14.3% of the positive results each. Therefore, insecticides are the most incriminated group of pesticides in intoxications (71.4%). Among the 21 positive cases, 52% were dogs, 19% cats, 14% poultry,10% ruminants and 5% other animal species (bees). Partition chromatography (HPLC) has been used to characterize the incriminated pesticides. The aim of this survey was to determine the frequency and the incidence of pesticide poisoning in domestic and farm animals in Tunisia. Then obtained results will be useful for the medical management of intoxicated animals.